2017
DOI: 10.4018/978-1-5225-2325-3.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rhizoremediation in Decontaminating Some Hazardous Pollutants

Abstract: Rhizoremediation is a natural biological base, multifactorial operation treatment method which highly depends to environmental factors especially in terrestrial environment as operation of remediation process. Interaction and relationship between microbial community and plant roots is specific attraction and advantages of this advanced treatment method. Decontamination efficiency and time could be highly manageable by operation and rhizoaugmentation. Rhizoremediation is advanced compact combination of phytoext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 171 publications
0
3
0
Order By: Relevance
“…This type of phytoremediation is going to be a major part of phytoremediation and nowadays have high concerning by scientists and research groups for both biodegradable and non-biodegradable pollutants. Rhizoremediation could be an advanced compact combination of phytoextraction, phytovolatilization, phytotransformation and phytostabilization (Farraji et al, 2017).…”
Section: Rhizoremediationmentioning
confidence: 99%
“…This type of phytoremediation is going to be a major part of phytoremediation and nowadays have high concerning by scientists and research groups for both biodegradable and non-biodegradable pollutants. Rhizoremediation could be an advanced compact combination of phytoextraction, phytovolatilization, phytotransformation and phytostabilization (Farraji et al, 2017).…”
Section: Rhizoremediationmentioning
confidence: 99%
“…Soils contaminated with elevated amounts of crude oil are often deficient in nitrogen. Legumes might be utilized in phytoremediation because of their symbiotic-association with nitrogen fixers (bacteria and fungi) and arbuscularmycorrhizal fungi (Farraji et al, 2017;McIntosh et al, 2017). The root system of leguminous plants generally is not as flourished as grasses to reach deeper soil layers (Safronova et al, 2011).…”
Section: Benefits Of Grasses Legumes and Trees In Phytoremediationmentioning
confidence: 99%
“…Common factors for selection of trees or grasses generally include: 1) resistance to contaminants, 2) tolerance to environmental conditions, 3) high productivity, 4) low bioaccumulation, 5) suitability for various soil types, and 6) native to avoid the introduction of invasive species. Several reports indicated that shrubs, grasses, herbs and trees are suitable candidates that can be utilized for phytoremediation (Farraji et al, 2017;Patel and Patra, 2017;Singha and Pandey, 2017;Shahsavari et al, 2016). Legumes (e.g.…”
Section: Plant Selection For Phytoremediationmentioning
confidence: 99%